Cases on teacher identity, diversity, and cognition in higher education - Breen, Paul, 1971- (Hershey PA : Information Science Reference, 2014)
"This thought-provoking collection of cases covers a range of educational contexts from preschool teaching in Europe to higher education in Australia and North America, and draws on expert knowledge of these diverse contexts, centered on a common theme of teacher identity"--
Includes bibliographical references and index.
BIL
Keywords: Teachers -- Training of -- Cross-cultural studies; Teachers -- In-service training -- Cross-cultural studies; Identity (Psychology); Teaching -- Social aspects; Multicultural education